From the Brundtland Commission to COP16 in Cali, keys to biodiversity conservation and sustainable development - Fanjul Benítez, Mario; Garrido García, Sergio; Martín Martín, Aurora Eloisa (Revista Española de Desarrollo y Cooperación, 2025)
From the Brundtland Commission to COP16 in Cali, passing through the Paris Declaration and the 2030 Agenda, a global consensus has emerged on the relationship between sustainable development, the environment, and biodiversity. Multilateral declarations, global regulatory frameworks, and regional and local initiatives have shown that integrating biodiversity protection into development policies generates social, economic, and environmental benefits. However, it is still necessary to strengthen global governance, expand climate finance mechanisms, and integrate gender and ecosystem-based approaches to address global challenges. In the face of advancing environmental denialism, coordinated global climate action based on evidence is key to rethinking a more ambitious and inclusive post-2030 agenda.
Keywords: cooperation; development; environment; biodiversity; climate finance; 2030 Agenda